2017
DOI: 10.1016/s2095-3119(16)61473-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of molasses on the fermentation characteristics of mixed silage prepared with rice straw, local vegetable by-products and alfalfa in Southeast China

Abstract: This experiment was conducted to study the effect of molasses on the fermentation characteristics of mixed silage ensiled rice straw and vegetable by-products with alfalfa. Mixture (202 g kg-1 dry matter (DM)) consisting of rice straw, broccoli residue and alfalfa at the ratio of 5:4:1 was ensiled with three experimental treatments: (1) no additives (control); (2) molasses at 2.5% (M1); (3) molasses at 5% (M2) on a fresh matter basis of mixture, respectively. All treatments were packed into laboratory-scale si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 24 publications
3
20
0
1
Order By: Relevance
“…In our study, BC in mulberry is 122.18 g lactic acid/kg of DM, which was higher than previous research (20.11 g lactic acid/kg of DM) (Trabi et al., ). The BC of mulberry was also higher than alfalfa (66–78 g lactic acid/kg of DM) (Tao et al., ; Wang, Wang, Zhou, & Feng, ; Wang et al., ), which was considered difficult to ensile well. In addition, Muck () reported that when the epiphytic population of LAB is greater than inoculants, LAB inoculant would not interfere with the silage fermentation.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, BC in mulberry is 122.18 g lactic acid/kg of DM, which was higher than previous research (20.11 g lactic acid/kg of DM) (Trabi et al., ). The BC of mulberry was also higher than alfalfa (66–78 g lactic acid/kg of DM) (Tao et al., ; Wang, Wang, Zhou, & Feng, ; Wang et al., ), which was considered difficult to ensile well. In addition, Muck () reported that when the epiphytic population of LAB is greater than inoculants, LAB inoculant would not interfere with the silage fermentation.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, immediately after the fermentation of the raw material, a variation in pH occurs, which reaches values between 5.5 and 6 due to the low concentration of lactic, acetic and propionic acid in the medium (Kung et al 2018). After 96 hours of fermentation in the silage there is a good production of lactic acid product of the action of lactic bacteria (Muck 2013), reducing the pH to values lower than 4.5, a pH lower than these values allows to obtain an optimal silage product nutritional, microbiological and organoleptic quality, without danger of transmitting diseases for animals (Wang et al 2016;Hartinger et al 2019;Tyrolová et al 2017).…”
Section: Resultsmentioning
confidence: 99%
“…In other words, besides modulating the DM of the forage, there was a need for sources of soluble sugars (RCJ or SM) to stimulate silage fermentation towards lactic acid production and to lower the pH. Such a harmonious effect was found when SBL was ensiled with the maize crop (17) or molasses was added to the silages (11,24). Since silages containing RCJ and SM had lower pH levels and greater BC than those that included SBL and pulp, it could be concluded that SBL ensiling was more successful when both SBP and SC sources were added to SBL.…”
Section: Discussionmentioning
confidence: 99%
“…Five milliliters of water extracted from the silage juice was used for measuring ammonia-N (8) according to the method described later in the relevant paper. Twenty milliliters of silage juice was kept at -20 °C to estimate lactic acid content using the calorimetric method (11) and total volatile fatty acid content was measured by steam distillation (12). Another 5 g of wet silage (equivalent to 0.5 g of DM) was also mixed with 30 mL of distilled water, homogenized for 3 m in a high-speed blender, and filtered through 4 layers of cheesecloth.…”
Section: Experimental Silagesmentioning
confidence: 99%